Our shared resilience: The collaboration of First Nations and local governments for flood mitigation in the Cowichan Valley - Yee, Holly Jeng Ting (Electronic version published by Vancouver Island University, 2023)
Flooding and the effects of climate change are increasing in frequency and intensity— the November 2021 atmospheric river is a stark reminder of the lasting impact on BC communities. This thesis explores the intersectionality between flood mitigation and the collaboration of First Nations and local governments in the Cowichan Valley. Findings conclude that flood mitigation must be integrated with holistic watershed management, rather than reactive emergency management measures—integrating Indigenous knowledge and decision-making is pertinent. Effective watershed governance begins with relationships that are inclusive of all levels of society: Indigenous and non- Indigenous communities, senior levels of government, community organizations, industry, and the public. This includes recognition of the effects of colonialism and the different governance systems for Indigenous and non-Indigenous communities in Canada. Relationships in the Cowichan Valley illustrate a strong network of collaborative community-level initiatives for flood mitigation, watershed management, and leadership. Thesis submitted in partial fulfillment of the requirements for the degree of Master of Community Planning in the Department of Community Planning, Faculty of Social Sciences, Vancouver Island University. https://viurrspace.ca/bitstream/handle/10613/27330/YeeThesis.pdf?sequence=6